Role of microRNAs in primary central nervous system lymphomas - Yu, Xin (Cell Prolif, 2016)
Primary central nervous system lymphomas (PCNSL) are extranodal non‐Hodgkin lymphomas arising exclusively inside the CNS, and account for about 3% of primary intracranial tumours. This tumour lacks systemic manifestations and prognosis of patients with PCNSL remains poor despite recent advancement of chemoradiotherapy. MicroRNAs are small non‐coding RNAs that post‐transcriptionally downregulate gene expression by binding to target mRNAs, inducing their degradation or translational repression. MicroRNAs play significant roles in almost all malignancy‐related biological processes, including cell proliferation, differentiation, apoptosis and metabolism. Many deregulated miRNAs has been identified in PCNSL but their biological significance remains to be fully elucidated. In this review, we summarize current evidence regarding the pathogenic role of PCNSL‐associated microRNAs and their potential applications for diagnosis and prognostication of this deadly disease.